2009
DOI: 10.1002/app.30349
|View full text |Cite
|
Sign up to set email alerts
|

Coatings on textiles for Cu(In,Ga)Se2 photovoltaic cell formation on textile carriers: Preparation of Cu(In,Ga)Se2 solar cells on glass‐fiber textiles

Abstract: Results are presented on the construction of a thin-layer photovoltaic cell on glass-fiber fabric. The unevenness of the fabric was first smoothed by the application of a high-temperature stable resin before photovoltaic layer deposition. We obtained an efficiency of light-tocurrent conversion of more than 8%. This constitutes a remarkably high value for a photovoltaic cell on a flexible substrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
(4 reference statements)
0
7
0
Order By: Relevance
“…[ 303 ] Copper indium gallium selenide (CIGS) photovoltaic cells fabricated on glass‐fiber textiles demonstrated PCE of >8% and some degree of stretchability due to the weaving textile structure. [ 158 ] Another interesting example is that of Lee et al. who developed stretchable solar cells based on GaAs microcells.…”
Section: Stretchable Photovoltaicsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 303 ] Copper indium gallium selenide (CIGS) photovoltaic cells fabricated on glass‐fiber textiles demonstrated PCE of >8% and some degree of stretchability due to the weaving textile structure. [ 158 ] Another interesting example is that of Lee et al. who developed stretchable solar cells based on GaAs microcells.…”
Section: Stretchable Photovoltaicsmentioning
confidence: 99%
“…Theoretical models have been employed to predict the mechanical properties of textiles. [ 154–157 ] The weaving nature of threads and fibers give rise to excellent mechanical properties such as flexibility [ 158–161 ] and stretchability. [ 162 ] One such example is the Lycra Spandex which can be stretched up to 200%.…”
Section: Strategies To Make Stretchable Electronicsmentioning
confidence: 99%
“…A flexible CIGS thin film coating was presented on glass-fiber-woven fabrics by Knittel et al in 2009 (shown in Figure 9 ), which achieved an efficency of 8.0% [ 123 ].…”
Section: Applying Flexible Photovoltaic Films and Coatings Onto Plmentioning
confidence: 99%
“… Photograph of the flexible copper indium gallium selenide thin film solar cell on glass fabric developed by Knittel et al Reprinted from [ 123 ] with permission from Wiley. …”
Section: Figurementioning
confidence: 99%
“…This approach was taken by Plentz et al [48] who produced low efficiency amorphous silicon PV cells on glass fibre fabrics having a dip-coating of polymer before the usual PV layers were applied, although cracking was mentioned as a potential problem. Higher efficiencies were achieved with CIGS cells deposited on to glass fibre fabric pre-coated with particle-filled resin that withstood the high processing temperatures of this type of cell [49]. Both of these inorganic PV cells use vacuum processes to apply the semiconductor: thermal evaporation of elements for CIGS and plasma enhanced chemical vapour deposition for a-Si:H. The electrical contacts are commonly applied by sputtering in a partial vacuum, whether they are metallic or a conducting transparent oxide.…”
Section: Photovoltaic Fabricsmentioning
confidence: 99%